2019
DOI: 10.32535/ijabim.v4i2.569
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of The Effect of Green Marketing on Consumer Purchasing Decisions on The Body Shop Gorontalo Product

Abstract: Consumer purchasing decisions are one of the classic problems that require further study by a marketer or company because they are motivated by consumer behavior that is always changing every time. Green marketing is one of the marketing concepts that aims to implement the company's marketing strategy in the environmental context, specifically in this study the products of the body shop Gorontalo. This study aims to answer whether green marketing has a significant influence on consumer purchasing decisions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Kotler and Armstrong (2016) contended that a consumer's purchase decision is a reflection of their decisiveness during the purchasing process as well as the processes that precede and follow it. The dynamics and traits of consumer behaviour-including what they buy, how they buy, why they buy, and how they use or dispose of what they buy-are essentially the foundation of consumer purchasing and buying decisions (Dixon-Ogbechi, 2019; Quang,2021Silaban et al2021 Consumers are known to be faced with myriads of determining factors in a purchasing decision state and it is essential for managers and marketers to know at every point how to influence consumer purchasing decision with the marketing mix elements of price, product, place and promotions (Wolok, 2019;Xue & Jo,2023).…”
Section: Concept Of Consumer Purchasing Decisionsmentioning
confidence: 99%
“…Kotler and Armstrong (2016) contended that a consumer's purchase decision is a reflection of their decisiveness during the purchasing process as well as the processes that precede and follow it. The dynamics and traits of consumer behaviour-including what they buy, how they buy, why they buy, and how they use or dispose of what they buy-are essentially the foundation of consumer purchasing and buying decisions (Dixon-Ogbechi, 2019; Quang,2021Silaban et al2021 Consumers are known to be faced with myriads of determining factors in a purchasing decision state and it is essential for managers and marketers to know at every point how to influence consumer purchasing decision with the marketing mix elements of price, product, place and promotions (Wolok, 2019;Xue & Jo,2023).…”
Section: Concept Of Consumer Purchasing Decisionsmentioning
confidence: 99%
“…Green"marketing adalah pemasaran produk yang termasuk ramah lingkungan baik dari proses pembuatannya hingga proses pemasarannya. Menurut Rahman et al (2017), Wolok (2019) indikator green marketing yaitu: Eco-Label (AMDK Ades menggunakan label yang menginformasikan produk ramah lingkungan); Eco-Brand (AMDK Ades adalah merek yang ramah lingkungan); Recycleable (AMDK Ades adalah produk yang dapat didaur ulang); Environmental Advertisement (AMDK Ades menggunakan iklan dengan tema lingkungan).…”
Section: Metode Penelitianunclassified
“…How this campaign helped The Body Shop in increasing its market share and profit. Research conducted by Wolok (2019) found that The effect of green marketing on consumer purchasing decisions on The Body Shop Gorontalo product related to environmental sustainability has a major effect on customer buying decisions. The variables used in this study are green marketing tools, environmentally sustainable goods, quality rates, environmentally friendly promotions, and environmentally friendly delivery.…”
Section: Literature Reviewmentioning
confidence: 99%